The Early Iron Age settlement of Artashat and problems of chrono-topography of the site (pre-Classical period) - Zardaryan, Mkrtich (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The archaeological study of the capital of ancient Armenia, Artashat, and the multiple approach to scholarly understanding of the materials found during its excavations, have been the focus of attention of researchers for more than four decades. Such an interest is caused by the unique role of this city in the history and culture of ancient Armenia, and its importance in the system of trans-regional cultural, economic and political relations between the states of ancient Western Asia and the Mediterranean.